The Use of Force Plate Technology to Measure Force Production Characteristics in Military Personnel: A Scoping Review of Methodological Reporting Practices. - Ladlow, Peter; Lunt, Kieran M.; Comfort, Paul; O'Sullivan, Oliver; Robles-Palazón, Francisco J; Ripley, Nicholas J.; McMahon, John J.; Masters, Natalie; Cassidy, Robyn P.; De Vecchis, Marina; Bell, Vanessa; Bennett, Alexander N.; et al. (Sports Medicine - Open, 2025)
Background: Force plates have become one of the most frequently used assessment tools in the field of strength and conditioning research and applied practice. Their use for measuring force production characteristics among military personnel is growing. The aim of this scoping review is to: (1) Describe the current evidence base underpinning the use of force plates to assess maximal and rapid lower-limb force production in military in three priority areas; occupational task performance, injury risk profiling, and rehabilitation, (2) Identify potential trends and/or differences by participants' sex, job role, and/or level of performance in tests, methodologies, and metrics selected, and (3) Consider gaps in the existing evidence base and questions that should be addressed in future research. Main Body: Nine hundred and eighty-five articles were identified across EBSCO and Ovid database platforms. After removing duplicates and applying the eligibility criteria, 40 articles were included in this review. Major differences/inconsistences in the methodological reporting of force plate 'preparation' (e.g., testing surface/flooring conditions, zeroing force plates and weighing participants during trials), 'execution' (e.g., verbal cueing and footwear conditions) and 'analysis' (e.g., software used to analyse force–time data, filters applied, thresholds used, metric selection and reliability testing) were found. The isometric midthigh pull (IMTP) and countermovement jump (CMJ) were the most used isometric and dynamic tests used, respectively. However, military researchers are commonly using no more than two metrics from each of these tests, with an emphasis towards only reporting outcome-based metrics (e.g., jump height) as opposed to movement strategy-based metrics. A more thorough review of the methodological reporting practices of the IMTP revealed most military researchers are using incorrect coaching instructions compared to standardised methodological guidelines or no instructions at all. When different expressions of force or power are reported using the CMJ, greater than half do not identify the phase of the jump it was calculated from. Conclusions: Across military populations, the methodological reporting standards and metrics selected when using force plate technology to inform 'occupational task performance', 'injury profiling' and 'rehabilitation' have been sub-optimal and sometimes incomplete. Force plate technology is currently under exploited when applied to military population research. Key Points: The use of force plate technology to measure maximal and/or rapid force production characteristics in military personnel is growing rapidly. The methodological reporting practices of force plate technology within military research practice is inconsistent and often poorly described. If military nations are to effectively use force plate technology in the future, greater awareness of metric selection and factors that influence the quality/accuracy of data outputs is warranted.